Peritoneal Dialysis Catheter Increases Leukocyte Recruitment in the Mouse Parietal Peritoneum Microcirculation and Causes Fibrosis. Issue 1 (January 2016) - Kowalewska, Paulina M.; Margetts, Peter J.; Fox-Robichaud, Alison E.
♦Background: The objective of this study was to examine the effects of a conventional dialysis solution and peritoneal catheter on leukocyte- endothelial cell interactions in the microcirculation of the parietal peritoneum in a subacute peritoneal dialysis (PD) mouse model. ♦Methods: An intraperitoneal (IP) catheter with a subcutaneous injection port was implanted into mice and, after a 2-week healing period, the animals were injected daily for 6 weeks with a 2.5% dextrose solution. Intravital microscopy (IVM) of the parietal peritoneum microcirculation was performed 4 hours after the last injection of the dialysis solution. Leukocyte-endothelial cell interactions were quantified and compared with catheterized controls without dialysis treatment and naïve mice. ♦ Results: The number of rolling and extravascular leukocytes along with peritoneal fibrosis and neovascularization were significantly increased in the catheterized animals compared with naïve mice but did not significantly differ between the 2 groups of catheterized animals with sham injections or dialysis solution treatment. ♦Conclusion: The peritoneal catheter implant increased leukocyte rolling and extravasation, peritoneal fibrosis and vascularization in the parietal peritoneum independently from the dialysis solution treatment.